Increasing Use of Advanced Practice Providers for Urological Office Procedural Care in the United States. Issue 2 (March 2017) - Erickson, Bradley A.; Han, Yu; Meeks, William; Gulig, Scott; Fang, Raymond; Annam, Kiran; Nepple, Kenneth G.
ABSTRACT : Introduction: : The United States population is aging, with increasing demand on the limited supply of urologists. Use of advanced practice providers could partly offset the growing demand for urological care. We evaluated the trends of independently performed/billed urological office procedural care by advanced practice providers. We hypothesized that the percentage and complexity of procedures performed independently by advanced practice providers is increasing. Methods: : We analyzed data from the 2003 to 2014 Medicare Physician/Supplier Procedure Summary Master File, available through the Centers for Medicare and Medicaid Services, for urological procedures with CPT® (Current Procedural Terminology) specialty codes of 97 (physician assistant) and 50 (nurse practitioner) for independently performed procedures. Trends through time for procedures were analyzed using the Mann‐Kendall test. Results: : Independently performed simple advanced practice provider procedures increased from 54, 549 to 230, 683 yearly from 2003 to 2014, with the most common procedures being measurement of post‐void residual, insertion of catheter and interpretation of uroflowmetry. Only 328 cystoscopies were billed independently by advanced practice providers in 2003 but this number increased to 2, 284 in 2014. The largest increase in technical procedures performed by advanced practice providers was for cystoscopic stent removal, which accounted for 0.05% of all procedures in 2003 and 1.3% in 2014 (24‐fold increase). Conclusions: : With the relative shortage of urologists more practices are relying on advanced practice providers for patient care. Independently performed procedures by these practitioners are increasing with time, including procedures of moderate complexity, clearly showing their evolving roles and responsibilities in the urology office.